Sustainable soils : - Wolf, Benjamin (Food Products Press, 2003)
This book shows the importance of organic matter in maintaining crop production. The addition of organic matter to soil is covered in great detail. This book is unique in that it draws on practical farming operations to illustrate many of the points discussed. The senior author has had almost 60 years of experience in solving production problems—many of which have been related to insufficient organic matter.